The phenotypic characteristics of polymorphonuclear neutrophils and their correlation with B cell and CD4+T cell subsets in thyroid-associated ophthalmopathy - Jin, Ke; Yao, Qian; Sun, Bin (Frontiers in Immunology, 2024)
Introduction: Thyroid-associated ophthalmopathy (TAO) is considered to be an organ-specific autoimmune disease. Polymorphonuclear neutrophils (PMN) have been implicated in the pathogenesis of TAO. However, little is known about the role of PMN in development of TAO, much less the relationship between PMN with B cells and CD4+T cells in TAO. Objective: To investigate the phenotypic characteristics of PMN and the relationship between PMN with CD4+T cell and B cell subsets in the pathogenesis of TAO Methods: The blood routine information wa's collected from 135 TAO patients, 95 Grave's disease without TAO (GD) patients, and 116 normal controls (NC) while flow cytometry was used to assess the surface marker expression of PMN and the level of T cell and B cell subsets in peripheral blood from 40 TAO patients, 17 GD patients, and 45 NC.The level of PMN, CD62L+PMN, CD54+PMN, CD4+T cells and Th17 cells displayed increased in TAO patients than NC while Treg cells were lower in the TAO group compared to the NC. There was no statistical differences in Th1, B cells plasma cells among the groups.PMN were positively correlated with Th17 cells, but not the Th1, Treg and plasma cells.In the present study, we found the percentage of PMN and PMN subsets cells was significantly higher in TAO than in NC, and PMN were positively correlated with Th17 cells. It suggests that PMN may involve in the immunopathogenesis of TAO and modulate the response of Th17 cells.